Sold out : how broken supply chains, surging inflation, and political instability will sink the global economy - Rickards, James (Portfolio/Penguin, an imprint of Penguin Random House LLC, 2022)
"Our global economy faces unprecedented challenges in the next few months. But whether we sink or swim depends on how prepared we are - and what we do now to thwart the coming collapse"--